2016
DOI: 10.1007/s12663-016-0915-5
|View full text |Cite
|
Sign up to set email alerts
|

Brain Abscess Potentially Resulting from Odontogenic Focus: Report of Three Cases and a Literature Review

Abstract: Oral surgeons should understand these characteristics of odontogenic brain abscess, in which the potentially causal odontogenic foci often lack acute symptoms. If other origins of infection are not found, it would be better to eliminate the potentially causal odontogenic foci for improvement of oral hygiene, however, the decision making criteria to eliminate suspected causal teeth is needed to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 20 publications
0
57
0
Order By: Relevance
“…Among these two sources of CNS infections (oral and sinusal) there is an important difference regarding microbiology. Streptococcus pneumoniae, Haemophilus influenzae and Moraxella catarrhalis are commonly associated with sinusitis while odontogenic infection is a mixed aerobic/anareobic infection (Eufinger & Machtens, 2001;Akashi et al, 2017). Common bacteria reported in oral infections, include gram positive organisms such as Streptococcus viridans, particularly the anginosus subgroup, and anaerobes such as Peptostreptococcus, Prevotella and Fusobacterium (Moazzam et al).…”
Section: Discussionmentioning
confidence: 99%
“…Among these two sources of CNS infections (oral and sinusal) there is an important difference regarding microbiology. Streptococcus pneumoniae, Haemophilus influenzae and Moraxella catarrhalis are commonly associated with sinusitis while odontogenic infection is a mixed aerobic/anareobic infection (Eufinger & Machtens, 2001;Akashi et al, 2017). Common bacteria reported in oral infections, include gram positive organisms such as Streptococcus viridans, particularly the anginosus subgroup, and anaerobes such as Peptostreptococcus, Prevotella and Fusobacterium (Moazzam et al).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Early detection can prevent further damage and spread to the cerebrum. 7,8 Urgent referral to a dentist or maxillofacial surgeon for diagnostic work-up and further treatment is essential in order to decrease the chance of serious complications. 9 The treatment procedure for a dental abscess, incision and drainage along with a root canal treatment, is straight forward if the patient is diagnosed quickly.…”
Section: Discussionmentioning
confidence: 99%
“…Chotai et al reviewed eight previously reported cases of brain abscess caused by G. morbillorum along with their own case; they found that most of the cases (62.5%) were associated with odontogenic infections and previous history of dental procedures. Parvimonas micra is an anaerobic Gram‐positive coccus also isolated from patients with brain abscess caused by odontogenic infection . Parvimonas micra is usually isolated from polymicrobial infections, and dental procedures were found to be risk factors for infection .…”
Section: Discussionmentioning
confidence: 99%